A survey of Mexican retail chain stores for fresh U.S. pork. (September 2016) - Huerta-Leidenz, N.; Howard, S.T.; Ruíz Flores, A.; Ngapo, T.M.; Belk, K.E.
Abstract: An overview of fresh US pork in the Mexican market was achieved by surveying fresh US pork packages (n = 342) for sale in five Mexican cities. Data on cut, primal/sub-primal from which the cut was sourced, subcutaneous and seam fat thicknesses, marbling scores, and presence of bone were collated. The most prevalent identifiable retail cuts were milanesa (thin slice of pork, breaded or non-breaded) and trozos (diced pork) derived primarily from the leg and accounting for 68% of the total US pork on sale. Over 90% of the retail cuts were trimmed to 3.2 mm or less of external fat and the average marbling score was 2.26. Differences in distribution and fat measures were observed with chain, location and socio-economic status of clientele indicating potential for a targeted marketing approach in Mexico. Highlights: Identifiable US pork cuts in the Mexican market were primarily milanesa and trozos The most common identifiable primal of US pork cuts was the leg Over 90% of the retail cuts were trimmed to 3.2 mm or less of external fat Average marbling score of the retail cuts was 2.26 Supermarket, location and target client influenced distribution and fat traits